Sistem Informasi Penggajian Berdasarkan Absensi Berbasis Web Pada PT. Catur Sentosa Anugerah Jambi - Huda, Nurul; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
Catur Sentosa Anugerah Jambi in processing employee salary still use microsoft excel and book still get trouble, such as : calculation salary is so slow and less than accurate due to the existence of an employee who works, the occurrence of no cheating in the recording the presence of employees and it difficult to obtain of data accuracy the presence of an employee to committed acts of a fine employees as a result of the delay in salary process employees take a long time in doing ' monthly salary report employees. The purpose of research is analyzing and design system information of employee salary using PHP programming language and MySQL database. Metodology of this research use waterfall model and unified model language using use case diagram, activity diagram, and class diagram. Conclusion of this system can featuring employee data, allowance data, bonus data, attendance data in structured and display reports required. Research advice are prototyped this system should be devised well and properly so that it will could be applied to PT. Catur Sentosa Anugerah Jambi